Multiple skin abscesses due to Nocardia neocaledoniensis: a case report and literature review - Jun Wang; Taigui Chen; Shijie Peng; Lianbao Li; Liling Wang; Jun Li; Wei He (BMC Infectious Diseases)
Abstract N. neocaledoniensis is a very rare infectious pathogen that causes human disease, particularly in immunocompromised individuals. In this case report, we describe the successful diagnosis of N. neocaledoniensis in a patient confirmed by mNGS and the treatment of multiple skin abscesses due to N. neocaledoniensis infection. mNGS is an important diagnostic method complementary to routine bacterial culture and identification methods, especially for rare, novel, co-infected pathogens, and pathogens that are difficult to culture. This report may provide a reference for the clinical treatment and diagnosis of N. neocaledoniensis infection in humans.